VEGFR2 but not VEGFR3 governs integrity and remodeling of thyroid angiofollicular unit in normal state and during goitrogenesis - Jeon Yeob Jang; Sung Yong Choi; Intae Park; Do Young Park; Kibaek Choe; Pilhan Kim; Young Keum Kim; Byung‐Joo Lee; Masanori Hirashima; Yoshiaki Kubota; Jeong‐Won Park; Sheue‐Yann Cheng; et al. (EMBO Molecular Medicine, 2017)
Abstract Thyroid gland vasculature has a distinguishable characteristic of endothelial fenestrae, a critical component for proper molecular transport. However, the signaling pathway that critically governs the maintenance of thyroid vascular integrity, including endothelial fenestrae, is poorly understood. Here, we found profound and distinct expression of follicular epithelial VEGF‐A and vascular VEGFR2 that were precisely regulated by circulating thyrotropin, while there were no meaningful expression of angiopoietin–Tie2 system in the thyroid gland. Our genetic depletion experiments revealed that VEGFR2, but not VEGFR3, is indispensable for maintenance of thyroid vascular integrity. Notably, blockade of VEGF‐A or VEGFR2 not only abrogated vascular remodeling but also inhibited follicular hypertrophy, which led to the reduction of thyroid weights during goitrogenesis. Importantly, VEGFR2 blockade alone was sufficient to cause a reduction of endothelial fenestrae with decreases in thyrotropin‐responsive genes in goitrogen‐fed thyroids. Collectively, these findings establish follicular VEGF‐A–vascular VEGFR2 axis as a main regulator for thyrotropin‐dependent thyroid angiofollicular remodeling and goitrogenesis.